Judicial Law-Finding in the Criminal Justice System: Harmonizing Legal Certainty and Substantive Justice - Irwan, Muhammad; Rahman, Ali; Amaliyah, Amaliyah (SIGn Jurnal Hukum, 2025)
The enactment of Law Number 1 of 2023 marks a fundamental paradigm shift in the Indonesian criminal justice system, prioritizing substantive justice over formal legal certainty. This shift radically transforms the role of a Judge from a mere mouthpiece of the law (bouche de la loi) to an active law-finder (rechtsvinder). However, the practice of law-finding in the field remains largely ad hoc and intuitive, creating a risk of inconsistency. Addressing this urgency, this research aims to formulate a systematic and accountable ideal concept of judicial law-finding to serve as an operational guide for Judges. Using a normative juridical method that integrates a statute approach, a conceptual approach, and a case approach to key court decisions, this study conducts a methodological reconstruction of the practice of judicial discretion. The primary finding is the formulation of a “judicial compass” built upon five mutually reinforcing fundamental principles: (1) proportionality, (2) transparency and accountability, (3) judicial consistency, (4) social responsiveness, and (5) dynamic equilibrium. These five principles collectively transform the law-finding process into a structured and rational approach. Thus, this ideal concept contributes both theoretically and practically by offering a coherent framework for Judges to execute the mandate of Law Number 1 of 2023, enabling them to harmonize legal values justly and measurably in every decision.